2017
DOI: 10.1038/bjc.2017.249
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of matrix metalloproteinase-8, transforming growth factor-β1 and vascular endothelial growth factor-C cooperatively contributes to the aggressiveness of oral tongue squamous cell carcinoma

Abstract: Background:Matrix metalloproteinase-8 (MMP-8) has oncosuppressive properties in various cancers. We attempted to assess MMP-8 function in oral tongue squamous cell carcinoma (OTSCC).Methods:MMP-8 overexpressing OTSCC cells were used to study the effect of MMP-8 on proliferation, apoptosis, migration, invasion and gene and protein expression. Moreover, MMP-8 functions were assessed in the orthotopic mouse tongue cancer model and by immunohistochemistry in patient samples.Results:MMP-8 reduced the invasion and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 58 publications
2
35
1
Order By: Relevance
“…Importantly, M2 macrophage is the phenotype displayed by most tumour-associated macrophages able to induce cancer growth [36]. We have also demonstrated that MMP8overexpressing HSC-3 cells, with significantly decreased cell invasion and migration, have increased MMP9 expression [12]. Here, we further showed that arrHSC-3 cells, also revealed to have reduced motility [19], had elevated MMP9 expression levels and a concomitant reduction in the amount of MMP2.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Importantly, M2 macrophage is the phenotype displayed by most tumour-associated macrophages able to induce cancer growth [36]. We have also demonstrated that MMP8overexpressing HSC-3 cells, with significantly decreased cell invasion and migration, have increased MMP9 expression [12]. Here, we further showed that arrHSC-3 cells, also revealed to have reduced motility [19], had elevated MMP9 expression levels and a concomitant reduction in the amount of MMP2.…”
Section: Discussionsupporting
confidence: 54%
“…Because of the diversity of the effects and functions of MMP9 reported in vitro, it would be highly important to evaluate whether the upregulated MMP9 in vivo has a true pathogenic effect or whether the upregulation is actually caused by the disease. The upregulation of MMP9 may also be a protective response of the host against the tumour [47], as in the case of MMP8 [12,55]. MMPs in vivo may play both pro-and antitumorigenic roles, depending on the nature of the cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMP-8 is a collagenase-2 that has oncosuppressive properties in different cancers. 47 It was already suspected that MMP-8 is produced at high levels by polymorphonuclear leukocytes (PMN) cells in the bone marrow and that the movement of MMP-8 is dependent on presence of the enzyme from PMN cells by degranulation. Nonetheless, recent studies have reported the presence of MMP-8 in mesenchyme-determined, non-PMN lineage cell lines, including human cartilage chondrocytes, synovial fibroblasts, and endothelial cells.…”
Section: Matrix Metalloproteinase-8mentioning
confidence: 99%